Hospital Policy in Providing Medicines outside the Provisions of Permenkes No. 28/2014 to BPJS Participant Patients - Joko Wahono (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2021)
This study analyzes criminal, civil and administrative legal responsibility for hospital policies in administering medicines outside the provisions of Permenkes Number 28 of 2014. This research is a normative legal research using a statutory approach (statue approach) and a conceptual approach (conceptual approach). The document study is used to collect legal material. The legal materials in this study consist of primary legal materials, secondary legal materials and tertiary legal materials. The health service that is often provided by the hospital to the public is a form of health service that is carried out outside the provisions of the regulations that must be carried out in accordance with the prevailing laws and regulations. The results showed that the implementation of medicine services for BPJS participant patients at the hospital was not in accordance with the Minister of Health Regulation No. 28 of 2014, BPJS participant patients were prescribed medicines outside the National Defense Forces to buy medicines at outside pharmacies at their own expense. The hospital can be held responsible for criminal, civil and administrative law. Therefore, it is hoped that hospitals and health workers, especially doctors, in carrying out their duties and obligations must comply with the prevailing laws and regulations in order to avoid the risk of legal liability.